Chapter 6 Keeping the faith? Examining the roles of faith and secularism in Syrian diaspora organizations in Lebanon - CARPI, ESTELLA (Taylor & Francis, 2020)
Since the start of the Syrian conflict in 2011, different types of Syrian-run organizations in Lebanon have been providing support and assistance to Syrian refugees. Whether in areas which are difficult for international providers to access, or in major towns and cities where international actors including the UN, INGOs and states have been providing assistance, Syrian diaspora organizations (DOs) have played a vital role. These DO initiatives have often taken the form of secular non-governmental organizations, or faith-based responses. At times, they have been actively funded by international donors or developed in formal partnership with UN agencies and INGOs, while in other contexts they have taken place on the margins of (or at times in ways that directly challenge) formal humanitarian aid structures. This chapter draws on lessons from anthropological, sociological, and IR studies, to construct a deeper understanding of secular and faith-based aid provision by members of displaced communities themselves in settings of the global South, which geographically (and geopolitically) neighbor new and ongoing crises. Based on long-standing research vis-à-vis local, national and international responses to displacement from Syria, it examines such endeavors through the framework of "refugee-led responses."